16-Cell stackable battery monitoring and management integrated circuit for electric vehicles. (June 2023) - Zhu, Guangqian; Qian, Libo; Li, Yongyuan; Guo, Wei; Ding, Ruixue; Yang, Yintang
Abstract: High-precision multi-channel battery monitoring integrated circuits (BMICs) assist battery management systems (BMSs) in effectively managing battery data, which is the key to improving the reliability of electric vehicles (EVs). This paper proposes a 16-cell stackable BMIC, in which a complete high-voltage multiplexing scheme and an incremental sigma-delta analog-to-digital converter (ADC) for monitoring. The chip performs two different data conversions in one monitoring instance, and the measurement error of the 16 channels is controlled within ±4 mV during calibration. The power management unit in the chip provides a stable internal module power supply voltage at an input voltage of 80 V, and the quiescent current is lower than 16 μA. As more cells must be stacked in the EV, the chip also supports chip-to-chip connections through current-mode communication to expand the number of stackable batteries. The chip was implemented based on a 0.18 μm BCD process, and the area of the proposed BMIC was 3 × 3 mm 2 .